Development of a model for the strategic management of corporate communication - Kasumba, Josephine (University of the Free State, 2003)
Abstract not available
Dissertation (M.A. (Communication Science))--University of the Free State, 2003
Keywords: Communication in organizations; Strategic management -- corporate communication; Corporate communication model